Análise bibliométrica da produção científica no Brasil sobre logística reversa entre 2017 e 2021 - Costa, Caio Cézar Campos da (Brasil, 2021)
This study aims to investigate the current state of the art of research in the field of Reverse Logistics, through the content analysis of publications related to the topic that are available in the google scholar database. A bibliometric analysis of works published between 2017 and 2021 in Brazil was carried out, mapping the current panorama of national publications on reverse logistics, analyzing national publications on reverse logistics in accordance with several points and identifying in each of them the existence of possible trends and/or patterns in scientific production related to the topic addressed. Therefore, this research has a quantitative approach, supported by bibliographical research, of a descriptive nature, with the application of descriptive statistics in the analysis of the results, in order to describe and summarize the set of collected data. The results obtained point to a series of indicators about the national scientific production on reverse logistics, such as: increasing interest in research in the area, most of the works analyzed are articles published in scientific journals, with emphasis on the Brazilian Journal of Development. The areas of concentration of periodicals with the largest contingent of productions on the subject are environmental management and sustainable development, while 44% deal with reverse logistics related to the environmental scope and 56% have a qualitative approach and 31% use bibliographical research in their work. Among the conclusions obtained, there is a growing interest in research in the area, which brings with it the improvement in epistemological and methodological indices in the national scientific production on the subject, a fact that is very good for the situation of national scientific research, as it can help Brazil better adapt to the National Solid Waste Policy (PNRS), as well as prompting society to adopt actions that seek to reduce the impact on the environment and other sustainable practices.